How Well Do We Measure Training? - Barron, John M.; Berger, Mark C.; Black, Dan A. (Journal of Labor Economics, 1997)
This article compares various measures of on-the-job training, from a new source that matches establishments and workers, allowing the authors to compare the responses of employers and employees to identical training questions. Establishments report 25 percent more hours of training than do workers, although workers and establishments report similar incidence rates of training. Both establishment and worker measures agree that there is much more informal training than formal training. Further, informal training is measured about as accurately as formal training. Finally, the authors show that measurement error reduces substantially the observed effect of training, in particular the effect of training on productivity growth. Copyright 1997 by University of Chicago Press.